Reference values for resting and post exercise hemodynamic parameters in a 6–18 year old population - Havasi, Katalin (Sci Data, 2020)
This database is the first large dataset of haemodynamic changes of normal-weight pupils during a field exercise test. Here, we present a dataset for anthropometric and hemodynamic parameters measured both during relaxation and after exercise containing 1,173,342 data segments from 65,345 acquisition points of 10,894 normal weight subjects, covering an age range of 6–18 years collected in a course of 12 years. Data acquisition was carried out under standardised measuring conditions and specifications. Hemodynamic parameters were measured in the normal-weight population with a new and simple Fit-Test which could facilitate new projects worldwide to study and compare cardiovascular fitness.